2017
DOI: 10.1136/bmjopen-2017-016626
|View full text |Cite
|
Sign up to set email alerts
|

Impact of policy support on uptake of evidence-based continuous quality improvement activities and the quality of care for Indigenous Australians: a comparative case study

Abstract: ObjectivesTo examine the impact of state/territory policy support on (1) uptake of evidence-based continuous quality improvement (CQI) activities and (2) quality of care for Indigenous Australians.DesignMixed-method comparative case study methodology, drawing on quality-of-care audit data, documentary evidence of policies and strategies and the experience and insights of stakeholders involved in relevant CQI programmes. We use multilevel linear regression to analyse jurisdictional differences in quality of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Ideally, CQI action and engagement occur within and between health service, regional and national levels of the health system, addressing systemic barriers within local contexts ( 11 ). In the Northern Territory, consistent and sustained policy and infrastructure support for CQI have resulted in a progressive uptake of evidence-based CQI activities and a stronger improvement of health-care performance than that of other jurisdictions ( 26 , 27 ). Performance improvement is attributed in large part to improved decision-making facilitated by the active and timely engagement of primary health-care teams in collation, analysis, participatory interpretation, and reporting of good quality local health care and health outcome data.…”
Section: Vertical Integration Of Cqi To Community and Broader Jurisdimentioning
confidence: 99%
“…Ideally, CQI action and engagement occur within and between health service, regional and national levels of the health system, addressing systemic barriers within local contexts ( 11 ). In the Northern Territory, consistent and sustained policy and infrastructure support for CQI have resulted in a progressive uptake of evidence-based CQI activities and a stronger improvement of health-care performance than that of other jurisdictions ( 26 , 27 ). Performance improvement is attributed in large part to improved decision-making facilitated by the active and timely engagement of primary health-care teams in collation, analysis, participatory interpretation, and reporting of good quality local health care and health outcome data.…”
Section: Vertical Integration Of Cqi To Community and Broader Jurisdimentioning
confidence: 99%
“…CQI is designed to improve health care by using data to identify where services are doing well and not so well, implementing and monitoring corrective action and then reviewing its effectiveness, in continuous improvement cycles. Studies, including the largest CQI program in Australia [16], have shown that with consistent policy and infrastructure it can facilitate ongoing improvement of PHC service delivery and subsequently, better health outcomes [16][17][18][19]. This largest program includes research in Aboriginal community controlled primary health care services [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies, including the largest CQI program in Australia [16], have shown that with consistent policy and infrastructure it can facilitate ongoing improvement of PHC service delivery and subsequently, better health outcomes [16][17][18][19]. This largest program includes research in Aboriginal community controlled primary health care services [16]. However, to our knowledge, there is no literature review specifically on the use of CQI strategies in improving service provision for unhealthy alcohol use in the PHC setting.…”
Section: Introductionmentioning
confidence: 99%
“…Primary drivers included staff capability, availability and use of information systems and decision support tools, embedding of CQI processes, and community engagement. We have also shown how consistent and sustained policy and infrastructure support for CQI enables large-scale and ongoing improvements in quality of care ( 3 ).…”
mentioning
confidence: 99%
“…Among a range of quality improvement strategies, CQI is characterized by iterative use of processes to identify quality problems, develop solutions, and implement and evaluate changes. Application of CQI in health care is evolving and evidence of their success continues to emerge ( 1 – 3 ).…”
mentioning
confidence: 99%